Bispyranopyrazoles as Green Corrosion Inhibitors for Mild Steel in Hydrochloric Acid: Experimental and Theoretical Approach - Singh, Priyanka; Kumar, Madhan; Quraishi, Mumtaz Ahmad; Jiyaul Haque; Singh, Gurmeet (American Chemical Society, 2018)
In the present study, we have synthesized two novel corrosion inhibitors BP-1 and BP-2 and evaluated their corrosion inhibition property on mild steel (MS) in acid solution through weight loss and electrochemical corrosion techniques. The corrosion test results reveal that both compounds inhibit corrosion by an adsorption mechanism and display inhibition efficiency more than 95% at a low concentration of 1.72 × 10−4 M. From the surface analysis of the protective film on MS, it was corroborated that adsorption of inhibitor molecules occurred on the MS surface through chemisorption, which further suppresses the corrosion rate. Density functional theory simulated data helps correlate the experimental trend with the theoretical study